Extending the scope of interprofessional education: Integrating insights from policy, management and economics for improved health outcomes - Shehzad, Shafqat (2016)
This study explores the potential of bringing innovations in public health education by drawing insights from the specialised disciplines of Economics, Policy and Management for their applications in the health sector. Working with subject experts from these disciplines can enhance the understanding of a working health care system and the necessary improvements for better health outcomes. Sole reliance on one field or skewed allocation of resources in certain areas may not result in achieving the desired health targets. Henceforth, overall integrated efforts for addressing the root causes of various health problems with an emphasis on good governance are important. This study presents a range of options for introducing new techniques in the curriculum design and development based on insights from the diverse disciplines of Economics, Policy and Management. The proposed innovative teaching and learning activities include students' involvement in policy dialogues through the departmental setup of Health Policy Networks (HPN); field activities to foster long-term industry linkages; institutional opportunities for students to interact with students of the related programmes in other international universities from the developing and developed countries; and the engagement of students to maintain records of visits and lessons learned for use in future interprofessional development. It is postulated that the typical pedagogy of teaching public health courses in isolation without interaction with experts/students from these diverse fields may only produce routine thinkers instead of healthcare leaders, system thinkers and innovators.